Analisis Regulasi Manajemen Sistem Keselamatan Instalasi Nuklir dalam Mewujudkan Ketahanan Energi Indonesia - Shafary, Ibnu Khathir; Sidik Boedoyo, Mohamad; Tumanggor, Muliahadi (Universitas Muhammadiyah Surakarta, 2024)
The rising energy demand in Indonesia has led to the planning of Nuclear Power Plants (NPP) as a sustainable solution, with implementation targeted around 2030. The government has emphasized the need for strict regulations, especially in safety management, reinforced by lessons from the Fukushima incident in Japan. This study underscores the critical role of regulatory analysis in the safety management of nuclear installations, which is essential for achieving energy security in Indonesia. By evaluating regulatory design and management system implementation, the research aims to identify key steps to support a safety culture in nuclear installations. Adopting a qualitative approach focused on policy analysis, this study evaluates aspects of Safety Management System Regulations in Nuclear Installations for Indonesia's Energy Security. The findings highlight the importance of structured management systems to enhance nuclear safety, providing a solid foundation for energy security. Strengthening regulations and implementing a systematic approach will ensure that Indonesia’s nuclear installations meet high safety standards, contributing positively to the country’s energy security.